1986
DOI: 10.1203/00006450-198608000-00014
|View full text |Cite
|
Sign up to set email alerts
|

An in Vitro Study of Choline Uptake by Intestine from Neonatal and Adult Rats

Abstract: MATERIALS AND METHODSthe developing small intestine are frequently different from those characterized in the intestine of mature animals (9-13).In the present studies, we examined the kinetics of choline uptake in the developing small intestine and compared these transport characteristics with those found in the intestine of mature animals.Animals. Adult, male Sprague-Dawley rats (Charles River Breeding Laboratory, Wilmington, MA), each weighing 100-125 g, were housed in stainless steel cages. Rat Chow (Ralsto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 12 publications
1
22
0
Order By: Relevance
“…Other studies conducted in animals, including the rat and mouse, confirm the role of carrier-mediated transport systems involved in the oral absorption of compounds such as choline from the gastrointestinal tract [57][58][59][60]. Similar studies have also reinforced that dietary constituents such as choline, L-carnitine and betaine are precursors to TMA [7,10,14,56,71,72].…”
Section: Dietary Precursorsmentioning
confidence: 81%
See 2 more Smart Citations
“…Other studies conducted in animals, including the rat and mouse, confirm the role of carrier-mediated transport systems involved in the oral absorption of compounds such as choline from the gastrointestinal tract [57][58][59][60]. Similar studies have also reinforced that dietary constituents such as choline, L-carnitine and betaine are precursors to TMA [7,10,14,56,71,72].…”
Section: Dietary Precursorsmentioning
confidence: 81%
“…The study by Zhang et al has revealed that there may be increased formation of TMA when the pure chemical form of these precursors is administered to humans as compared to the ingestion as a component of whole food [6]. Studies have also confirmed that choline and L-carnitine undergo carrier mediated absorption [57][58][59][60][61][62][63], meaning that the administration of higher oral doses of these precursors would result in increased generation of TMA [10]. However, Gas chromatography (solid-phase microextraction) Urine Aqueous 0.8 µM to 157 µM Mills et al [39] Gas chromatography (derivitization with 2,2,2-trichloroethylchloroformate) Urine Blood 1pmol to 250 pmol Da Costa et al [41] Fast atom bombardment-mass spectrometry Urine 7 µM to 135 µM Mamer et al [46] Proton nuclear magnetic resonance spectroscopy Urine Abeling et al [44] HPLC (conductimetric detection) Urine Marzo et al [43] HPLC (refractive index) Urine Marzo et al [43] differences in gastrointestinal physiology between animals and humans [64] (for instance the human small intestine is reported to have a lower absorptive capacity for L-carnitine than the rat [52]) could mean that the fate of these chemical precursors may also be dissimilar.…”
Section: Dietary Precursorsmentioning
confidence: 90%
See 1 more Smart Citation
“…Choline is absorbed from the small intestine via mediated transport which is half saturated at choline concentrations in the intestines of 200-300 µM [39][40][41]. If choline-rich food is ingested, and the concentration of choline in the small intestine exceeds the transport capacity, choline reaches the large bowel.…”
Section: Metabolism Of Tmaomentioning
confidence: 99%
“…Choline is present as free choline and choline esters in the diet (5), and these forms of choline are absorbed differently in the intestines. Free choline is absorbed in the small intestine via mediated transport (6), whereas phosphatidylcholine is not converted to choline within the intestinal lumen [it is absorbed intact via the lymphatic system or is hydrolyzed by pancreatic lipases and absorbed as glycerophosphocholine (7)]. On the basis of these differences, dietary free choline (the substrate for trimethylamine formation by bacteria) but not dietary phosphatidylcholine should result in TMAO formation.…”
Section: Introductionmentioning
confidence: 99%